2016
DOI: 10.1002/iid3.96
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atopy and asthma on immune responses in inner‐city adults

Abstract: Asthma in the inner‐city population is usually atopic in nature, and is associated with significant morbidity and mortality. However, the underlying immune abnormalities that underlie asthma in urban adults have not been well defined. We investigated the influence of atopy and asthma on cytokine responses of inner‐city adult women to define immune abnormalities associated with asthma and atopy. Blood samples were collected from 509 of 606 inner‐city women enrolled in the Urban Environment and Childhood Asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Interestingly, in that study 11 of the 19 children had a medical diagnosis of atopy or allergy. A study looking at adults also showed that atopy and asthma were also associated with the production Th2 cytokines, including IL-5 in response to TT stimulation [75], suggesting that in individuals biased towards IL-5 production to TT corresponds with strong responses to the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in that study 11 of the 19 children had a medical diagnosis of atopy or allergy. A study looking at adults also showed that atopy and asthma were also associated with the production Th2 cytokines, including IL-5 in response to TT stimulation [75], suggesting that in individuals biased towards IL-5 production to TT corresponds with strong responses to the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…They identified chemokine (C‐X‐C motif) ligand (CXCL)‐1, IL‐5, IL‐8 and IL‐17 in inner‐city African American children, which were positively associated with ‘easy‐to‐control’ asthma [7]. In adults with atopic asthma, elevated T2 cytokine responses (IL‐4, IL‐5, IL‐13) to allergenic and antigenic stimuli were observed compared to non‐atopic asthmatics [8]. In the Unbiased BIOmarkers in PREDiction of respiratory disease outcomes (U‐BIOPRED) project, Kuo et al .…”
Section: Introductionmentioning
confidence: 99%